The Role of Intuition in the Creative Process of Expert Chefs. (14th September 2015) - Stierand, Marc; Dörfler, Viktor
Abstract: Scholars studying intuition are frequently focusing on decision takers and to this day, they conceptualize intuition as a form of judgment. More recently, the notion of intuition in creativity has been challenged by the argument that although the creative process may contain intuitive judgments, any creative idea or solution is essentially the result of intuitive insight. This interpretivist study seeks an increased understanding of the role of intuition in the creative process by providing empirical evidence from in‐depth interviews with expert chefs. The findings show that the interviewees describe their experiences of the creative process consistent with how the literature describes intuition and explain intuitive insight and judgment as instantaneous yet distinct and rapid processes.